A versatile fibre-based setup for two-line atomic fluorescence thermometry in aerosol processes. (February 2022) - Labus, Markus; Lang, Peter; Bahr, Leo; Huber, Franz J.T.; Will, Stefan
Highlights: Versatile split calibration-free TLAF setup. Novel hexagonal close-packed calibration burner for aerosol applications. Improved hyperfine structure model for temperature evaluation. Abstract: A calibration-free two-line atomic fluorescence (TLAF) setup was designed for optical high-precision temperature measurements in combustion processes, with a focus on a high practical applicability in combustion systems. The setup is split into a mobile fibre-connected sensor head and a separate laser arrangement allowing for versatile application, e.g. especially for future application in nano particle synthesis processes even with limited optical access. As many standard burners for premixed flames are problematic regarding aerosol feeding because of clogging, a novel homogenous and laminar hexagonal close-packed (HCP) burner suitable for future calibration purposes was implemented. The burner consists of an HCP sphere matrix and allows for high-precision temperature measurements as well as the absolute measurement of the wavelengths of the hyperfine structure of the indium (In) transitions 6 2 S1/2 →5 2 P1/2 and 6 2 S1/2 →5 2 P3/2 within a combustion environment. To improve the quality of the fit of the hyperfine spectra, we furthermore included both most abundant indium isotopes In115 and In113 into the calculation model, thereby minimizing residuals between measured and modeled data and thus systematic errors compared to previous approaches. In the presented work, flame temperatures at atmospheric pressure with various air-fuel ratios and heights above the burner surface could be determined from single-scan spectra with a high average precision of 34 K.